Incidence of adverse events in health care: comparison between states in the South Region (Research, Society and Development, 2022)
Objective: to analyze the incidence of adverse events reported to the Health Surveillance Notification System from September 2019 to August 2020, in the states of Rio Grande do Sul and Santa Catarina. Method: exploratory, descriptive and analytical research with a quantitative approach. The variables were analyzed using the Bioestat program and submitted to the Shapiro Wilke and Mann Whitney tests, with a significance level of 5%. The Results: data demonstrate a significant difference between the incidences of Adverse Events reported between states. In addition, from the Box-Plots, it is inferred that the state of Santa Catarina has a higher incidence than Rio Grande do Sul. Conclusion: despite having a smaller population and fewer registered Patient Safety Centers, the state of Santa Catarina reported a higher number of notifications than Rio Grande do Sul. These findings are relevant for a broader analysis in relation to possible underreporting and its conditioning factors.